2022
DOI: 10.3390/metabo12040356
|View full text |Cite
|
Sign up to set email alerts
|

Metabolites Associated with Memory and Gait: A Systematic Review

Abstract: We recently found that dual decline in memory and gait speed was consistently associated with an increased risk of dementia compared to decline in memory or gait only or no decline across six aging cohorts. The mechanisms underlying this relationship are unknown. We hypothesize that individuals who experience dual decline may have specific pathophysiological pathways to dementia which can be indicated by specific metabolomic signatures. Here, we summarize blood-based metabolites that are associated with memory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 73 publications
5
6
0
Order By: Relevance
“…In line with our ST findings, they highlight APOE - and amyloid-associated decreases in a number of PCs, a class of phospholipid linked to memory decline. 70 Although a handful of PCs were highest in the E4 5XFAD brain, the majority of PCs were present in lower concentrations relative to the other groups, consistent with findings from the postmortem human brain. 67 Regional segregation of lipid concentrations revealed that for most PCs, APOE -dependent changes in lipid concentrations were more striking in the isocortex, hippocampus, and fiber tracts relative to other brain regions.…”
Section: Discussionsupporting
confidence: 80%
“…In line with our ST findings, they highlight APOE - and amyloid-associated decreases in a number of PCs, a class of phospholipid linked to memory decline. 70 Although a handful of PCs were highest in the E4 5XFAD brain, the majority of PCs were present in lower concentrations relative to the other groups, consistent with findings from the postmortem human brain. 67 Regional segregation of lipid concentrations revealed that for most PCs, APOE -dependent changes in lipid concentrations were more striking in the isocortex, hippocampus, and fiber tracts relative to other brain regions.…”
Section: Discussionsupporting
confidence: 80%
“…18 A recent systematic review showed metabolites from sphingolipids and the sphingolipid metabolism pathway are important for both memory and gait impairments. 19 In agreement with the metabolic origin of dual decline, MCR is found to be associated with obesity-related polygenetic risk scores for body mass index and waist circumference. 20 It is worth noting that the lysoPCs are the main building blocks for cardiolipin, an essential lipid for the regulation and assemblage of electron transport complexes and mitochondrial morpho-functional architecture.…”
Section: Putative Mechanisms Linking Dual Decline and Dementiasupporting
confidence: 57%
“…Those with dual decline also showed the most extensive alterations in metabolomic profiling of lipids and lipid metabolism, especially lysophosphatidylcholines (lysoPCs) 18 . A recent systematic review showed metabolites from sphingolipids and the sphingolipid metabolism pathway are important for both memory and gait impairments 19 . In agreement with the metabolic origin of dual decline, MCR is found to be associated with obesity‐related polygenetic risk scores for body mass index and waist circumference 20 .…”
Section: Putative Mechanisms Linking Dual Decline and Dementiamentioning
confidence: 88%
“…A large-scale cohort study comparing 150 healthy individuals using non-targeted plasma LC–MS metabolomics revealed the levels of phospholipids (phosphocholine), phosphoserine, and prostaglandin changed with aging [ 11 ]. A recent systematic review of 39 studies on memory and gait decline with aging found that the five most age-correlated plasma or serum metabolites were sphingolipids, fatty acids, phosphatidylcholines, amino acids, and biogenic amines [ 41 ]. These results suggest that lipid metabolism is closely associated with aging by affecting membrane permeability, energy metabolism, signaling pathways, and gene expression; the decreased glycerophosphocholine in the CSF of the old age group in our study suggests defective cell membrane turnover and BBB breakdown in the aged brain.…”
Section: Discussionmentioning
confidence: 99%